2018
DOI: 10.1159/000495328
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-1290 Promotes Aggressiveness in Pancreatic Ductal Adenocarcinoma by Targeting IKK1

Abstract: Background/Aims: MicroRNAs (miRNAs) are a group of non-coding RNAs that play diverse roles in pancreatic carcinogenesis. In pancreatic ductal adenocarcinoma (PDAC), NF-kB is constitutively activated in most patients and is linked to a mutation in KRAS via IkB kinase complex 1 (IKK1, also known as IKKa). We investigated the link between PDAC aggressiveness and miR-1290. Methods: We used miRCURYTM LNA Array and in situ hybridization to investigate candidate miRNAs and validated the findings with PCR. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 40 publications
2
20
0
1
Order By: Relevance
“…Several literatures revealed that miRNAs are involved in the development of human diseases, including malignancies [16][17][18]. Currently, abundant miR-NAs, such as miR-1290 [19], miR-216b [20], and miR-454 [21], were illustrated to be abnormally expressed in PDAC patients. Significantly, miR-340-5p was served as a downstream target of LINC00857 by visiting bioinformatics software.…”
Section: Introductionmentioning
confidence: 99%
“…Several literatures revealed that miRNAs are involved in the development of human diseases, including malignancies [16][17][18]. Currently, abundant miR-NAs, such as miR-1290 [19], miR-216b [20], and miR-454 [21], were illustrated to be abnormally expressed in PDAC patients. Significantly, miR-340-5p was served as a downstream target of LINC00857 by visiting bioinformatics software.…”
Section: Introductionmentioning
confidence: 99%
“…However, considering the inconsistency among these miRNA profiling studies, we carried out an integrated analysis of three GEO datasets and discovered that serum miR-1290 and miR-1246 were significantly upregulated in PC patients. Moreover, previous studies have shown that miR-1290 and miR-1246 both underwent significant changes in PC tissues compared with non-cancer specimens [19][20][21]. Hence, we inferred that these two miRNAs may be novel biomarkers for PC and explored the potential of candidate miRNAs (miR-1290 and miR-1246) for PC diagnosis in this study.…”
Section: Discussionmentioning
confidence: 83%
“…Results of logistic analyses showed that both of them were determined as independent risk factors for the onset of PC, indicating that both miR-1290 and miR-1246 might play an important role in oncogenesis of PC. Ta N et al [20] declared that miR-1290 functioned as a tumor oncogene and enhanced PC cell proliferation, invasion, and migration by directly targeting the 3' UTR of IKK1 [21]. Meantime, a previous study also proved that miR-1290 could promote pancreatic ductal adenocarcinoma malignant progression by silencing the FOXA1/2, which was involved in epithelial-to-mesenchymal transitions [23].…”
Section: Discussionmentioning
confidence: 99%
“…Recent therapeutic research showed that restoring either miR-143 or miR-145 significantly inhibited pancreatic metastasis [73,80]. Another study by Ta et al showed that NF-kβ, constitutively active in pancreatic cancer patients, is promoted by miR-1290, relates to the expression of IKK1 [91], and is implicated in the downregulation of miR-146a, suggesting its role as a tumor suppressor in most cancers. Meanwhile, miR-27a becomes highly upregulated and could be a target for therapeutics during metastasis.…”
Section: Factors Crucial For the Formation Of Lung Metastasismentioning
confidence: 99%
“…Interestingly, both miR-1290 and miR-1246. because of their detectability in serum, are being studied as potential biomarkers [91,96]. In metastasis, miR-34a is found downregulated since it is a direct target of TP53 to reduce pro-inflammatory cytokines.…”
Section: Factors Crucial For the Formation Of Lung Metastasismentioning
confidence: 99%